Therapeutic Use of Video Games in the Treatment of Posttraumatic Stress Disorder (PTSD): A Case Study of an Immersed 10-Year-Old Boy - Bean, Anthony (Journal of Psychology and Psychotherapy Research, 2022)
Working therapeutically with video gamers has almost entirely consisted of an overshadowing addiction perspective. This undoubtedly leads any therapist working with video gamers to assume they are addicted, further guiding treatment into a reduction or complete termination of all video games. To date, there are no known uses of video games in a clinical setting as therapeutic tools. This case study illustrates use of Archetypal and Jungian therapies prescribing video games for a 10-year-old male diagnosed with Posttraumatic Stress Disorder (PTSD). Video games were utilized as a main form of inclusion and immersion playability. He experienced a reported improvement in his symptoms across his environments. Parental involvement, therapist’s knowledge of video game worlds, and using video games’ heroic motifs were critical to the client’s understanding of himself. If an addiction lens had been utilized, the client may not have been successful. Through this comprehensive study, the research will showcase that clinicians should aim to think outside of the addiction lens while working with video gamers. As therapists are presumed to be experts in communication, it makes sense to utilize the language of the video game world to communicate and understand where the client may be presently situated. Utilizing this immersive experience opens the door for a more collaborative therapy, increasing communication about video games, playing, and extrapolating players’ experiences into real life contexts.